Nature-Based Solutions to Climate Change Adaptation in Urban Areas: Linkages between Science, Policy and Practice - Kabisch, Nadja; Korn, Horst; Stadler, Jutta; Bonn, Aletta (Theory and Practice of Urban Sustainability Transitions, 2017)
climate change; cities; society; biodiversity; mitigation; impact